2004
DOI: 10.1007/bf02975123
|View full text |Cite
|
Sign up to set email alerts
|

Voltammetric studies of Cu-adriblastina complex and its effect on ssDNA-adriblastina interaction atin situ mercury film electrode

Abstract: Adriblastina, a cancerostatic anthracycline antibiotic, causes considerable oxidative damage to DNA molecules. The interaction of this compound with DNA was investigated using Osteryoung square wave stripping voltammetry (OSWSV) and cyclic voltammetry (CV) at an in situ mercury film electrode. It was found that the equilibrium constant of the bonded oxidized form of the drug was 63 times bigger more important than that of the bonded reduced form. Copper forms 1 metal: 2 drug stoichiometry complex which is high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…At acidic and neutral pH in addition to a reversible reduction peak corresponding to two-electron reduction an irreversible reduction peak has been observed for anthracyclines and hydroxy-9,10-anthraquinones. Several studies on the electrochemical behavior of adriamycin (doxorubicin hydrochloride) and daunorubicin (daunomycin) (Scheme 3) by different researchers have been extensively carried out over a few decades [72][73][74][75][76][78][79][80][81][82][83][84][85][86]. Rao et al [72] and Molinier-Jumel et al [73] have discussed the mechanism involved in the reduction of anthracyclines at mercury electrodes and attempted to correlate the observed behavior with their therapeutic actions.…”
Section: Electrochemical Reduction In Buffered Aqueous Mediamentioning
confidence: 99%
See 1 more Smart Citation
“…At acidic and neutral pH in addition to a reversible reduction peak corresponding to two-electron reduction an irreversible reduction peak has been observed for anthracyclines and hydroxy-9,10-anthraquinones. Several studies on the electrochemical behavior of adriamycin (doxorubicin hydrochloride) and daunorubicin (daunomycin) (Scheme 3) by different researchers have been extensively carried out over a few decades [72][73][74][75][76][78][79][80][81][82][83][84][85][86]. Rao et al [72] and Molinier-Jumel et al [73] have discussed the mechanism involved in the reduction of anthracyclines at mercury electrodes and attempted to correlate the observed behavior with their therapeutic actions.…”
Section: Electrochemical Reduction In Buffered Aqueous Mediamentioning
confidence: 99%
“…The peak current is directly proportional to the concentration of doxorubicin and using this linear relation concentrations of doxorubicin in the unknown sample has been determined with very high precision [80]. El-Hady et al [81] studied the electrochemical behavior of Cu(II) complex of adriblastina (adriamycin or doxorubicin hydrochloride) and its interaction with DNA by square wave voltammetry. They were able to show that the electrochemical reduction of such a complex is reversible but irreversibility increases with increase of pH.…”
Section: Electrochemical Reduction In Buffered Aqueous Mediamentioning
confidence: 99%
“…The effect of deposition time on peak current in SWV studies has been reported elsewhere. 27,28 3.1.7 Influence of pH. pH plays key role in decreasing or increasing peak current values of a particular species because some reactions are more favored at one pH, while hindered or slowed down at others.…”
Section: Effect Of Deposition Timementioning
confidence: 99%
“…cesius. They are commonly used in the treatment of a number of diverse malignant tumours, including acute lymphoblastic and myeloid leukaemia, non-Hodgkin's and Hodgkin's lymphoma, multiple myeloma, lung, ovarian, gastric, thyroid and breast carcinoma, sarcomas, neuroblastoma, nephroblastoma etc [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%